An azaanthracene alkaloid from Polyalthia suberosa - Patoomratana Tuchinda (2018)
An azaanthracene alkaloid, 1-aza-9,10-dimethoxy-4-methyl-2-oxo-1,2- dihydroanthracene (kalasinamide) has been isolated from the stems of Polyalthia suberosa. In addition, the known N-trans-feruloyltyramine and N- trans-coumaroyltyramine are also reported from the same source. The structures were elucidated by spectroscopic methods. (C) 2000 Elsevier Science Ltd.